2015
DOI: 10.1016/j.jhin.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Preventing invasive candida infections. Where could we do better?

Abstract: Invasive candidiasis is associated with high mortality rates, ranging from 35% to 60%, in the range reported for septic shock. The epidemiology and pathogenesis of invasive candidiasis differ according to the patient's immune status; the majority of cases in immunocompromised hosts are candidaemia, whereas non-candidaemic systemic candidiasis accounts for the majority of cases in critically ill patients. In contrast to candidaemia, non-candidaemic systemic candidiasis is difficult to prove, especially in criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 59 publications
1
50
0
3
Order By: Relevance
“…The population candidemia rate is estimated at 5/100,000. We assumed 35% of candidemia episodes occur in ICU, and that the rate of Candida peritonitis is ~50% of the ICU candidemia rate [17][18].…”
Section: Methodsmentioning
confidence: 99%
“…The population candidemia rate is estimated at 5/100,000. We assumed 35% of candidemia episodes occur in ICU, and that the rate of Candida peritonitis is ~50% of the ICU candidemia rate [17][18].…”
Section: Methodsmentioning
confidence: 99%
“…These results agreed with rates previously published about candiduria nosocomial, when was found low rates of antifungal resistance to amphotericin B, fluconazole, voriconazole and caspofungin. 23 In opposite, others studies found high rate of antifungal resistant to Candida species obtained from urine samples from patients in intensive care unit and patients with candiduria. 24,25 In our study, when we tested the azole compounds we found two C. albicans fluconazole and ketoconazole resistant.…”
Section: Discussionmentioning
confidence: 96%
“…Despite their severity, there are several limitations to the final diagnosis of invasive infections (Eggiman et al, 2015[15]). Hemocultures provide positive results in only 50-70 % of cases (Calandra et al, 2016[5]).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that bacterial infections have historically received more attention than the fungal ones, preventive prescription and escalation of broad-spectrum antibiotics is common. Thus, antibiotic use represents an additional risk factor for the occurrence of invasive fungal infections (Delaloye and Calandra, 2014[12]; Eggiman et al, 2015[15]; Muskett et al, 2011[28]) due to the selective pressure on the pathogenic microorganisms.…”
Section: Discussionmentioning
confidence: 99%